UNIVERSITIES SPORTS MANAGERS ON DUAL CAREER - Ābeļkalns, Ilvis; Kravalis, Ivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The aim of this article is to give an overview on possibilities for students – top athletes to combine their career in respective sports field with studies in different Latvian higher education establishments. Authors of the article analyse scientific literature and the opinions expressed in the individual interviews of the heads of higher education institutions of Latvia as well as officials of State departments responsible for Sports regarding support opportunities that are important for the promotion of dual careers for students – top athletes. Authors of the article study and analyze the possibilities for top athletes to obtain higher education and opportunities to improve the training process. The article gives a theoretical insight and analyzes the results of surveys led by sports managers in Latvia's higher education institutions. After processing the responses, recommendations for the management of the dual career process in higher education institutions have been developed, which could help to achieve a successful implementation of dual career for athletes in Latvia.